2020
DOI: 10.3389/fphar.2020.596046
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Intercellular Communication Negatively Regulates Cadmium-Induced Autophagy and Inhibition of Autophagic Flux in Buffalo Rat Liver 3A Cells

Abstract: Cadmium is an important environmental pollutant that poses a serious threat to the health of humans and animals. A large number of studies have shown that the liver is one of the important target organs of cadmium. Stimulation of cells can lead to rapid changes in gap junction intercellular communication (GJIC) and autophagy. Previous studies have shown that cadmium can inhibit GJIC and induce autophagy. In order to understand the dynamic changes of GJIC and autophagy in the process of cadmium-induced hepatoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In addition, we can also explore the role of gap junction intercellular communication (GJIC) function in VSMC autophagy. It has been found that GJIC negatively regulated autophagy and inhibited autophagy flux ( Zou et al, 2020 ). In summary, ox-LDL prevented VSMC autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we can also explore the role of gap junction intercellular communication (GJIC) function in VSMC autophagy. It has been found that GJIC negatively regulated autophagy and inhibited autophagy flux ( Zou et al, 2020 ). In summary, ox-LDL prevented VSMC autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a dynamic and complex process; impairment of any of its elements can impact autophagic flux. Cd elevates the level of autophagy in rat BRL3A cells [ 30 ] and results in higher levels of autophagy and blocked autophagic flux in mouse hepatocytes AML12 cells [ 29 ]. Ni Gao et al [ 31 ] found that Tau can inhibit hepatic autophagy by activating the PPARγ-mTORC2 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…BRL3A cells were seeded in 24-well plates and cultured to approximately 80% confluence, followed by treatment with 80 mM Tau and/or 5 μM Cd for 6 h. Then, cells were photographed with the Leica DMIRB inverted microscope. The doses of Cd and Tau were determined based on previous studies [ 30 , 41 , 42 , 43 ]. While referring to the previous studies, we also screened the concentration of Tau, and finally 80 mM Tau was used to treat the cells in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The Cd-induced decrease in Cx43 levels in BRL 3A cells as well as the internalization and degradation of Cx43 may have blocked the transmission of toxins between cells through gap junctions. Previously, other members of our group used 18β-glycyrrhetinic acid, a compound that promoted Cx43 internalization, to alleviate the damage caused by Cd exposure to rat hepatocytes [ 52 ]. The results from the present study are concordant with their results.…”
Section: Discussionmentioning
confidence: 99%